Implementasi Kurikulum Merdeka sebagai Pembentukkan Generasi Sains yang Berkarakter: Ditinjau dari Visi Misi dan Kompetensi Pendidik MAN 1 Kota Bandung - Arribah Auliani; Melfiana Khoirunnisa; Ahmad Syaeful Rahman (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
To face the challenges of the 21st century, we need superior human resources who are not only smart but also have character. Education is the main key, therefore the curriculum as the basis for learning planning must be relevant to the needs of the times. The government responded by implementing the Merdeka Curriculum, which integrates the Pancasila and Rahmatan lil Alamin (P5RA) Student Profile Strengthening Project. MAN 1 Bandung City has seriously implemented the Merdeka Curriculum after the pandemic, in accordance with its vision and mission as a superior madrasa. This study focuses on the relevance of implementing the Merdeka Curriculum at MAN 1 Bandung City, by paying attention to the school's vision and mission with the competence of educators who support the sustainability of the Merdeka Curriculum at MAN 1 Bandung City. This research uses a qualitative approach with a descriptive type. The results showed that the vision and mission of MAN 1 Kota Bandung is in line with the objectives of the Merdeka Curriculum. The implementation of the Merdeka Curriculum at MAN 1 Kota Bandung, namely adopting a “moving class” program to adapt learning to student interests, is supported by methods such as PJBL and PBL. The majority of teachers understand the Merdeka Curriculum after intensive training. Senior educators sometimes face technological obstacles, but are still able to compile learning outcomes and integrate P5RA.